Success Factors of Task Management Application in The Business Service Division of PT Telkom Indonesia - Arif Imam Suroso; Nur Hasanah; Mulyani (Indonesian Journal of Business and Entrepreneurship, 2023)
The success of the company's operational management is formed by the success of building and running the information system. PT Telkom Indonesia is using a task management application to manage sales activity. Success assessment of the application uses the Delone & Mclean model. This study aims to analyze factors that influence the success of implementation task management based on the perspective of the direct user called the account manager. Respondents in this study are account managers with a total sample of 150 people. The data collection technique uses a questionnaire and is analyzed using the SEM-PLS method. The results of this study indicate that system quality has a significant effect on usage and user satisfaction, information quality has no significant effect on usage and user satisfaction, and service quality has no significant effect on usage but has a significant effect on user satisfaction. Usage has a significant effect on user satisfaction. Furthermore, user satisfaction and usage have a significant effect on net benefits. Therefore the Delone and Mclean model is confirmed to be used in assessing the success of the implementation task management at the Business Service Division PT Telkom Indonesia. Keywords: account manager, delone & mclean, information system, sem-pls, task management